2013
DOI: 10.1182/blood-2012-06-438762
|View full text |Cite
|
Sign up to set email alerts
|

Impaired thrombin-induced platelet activation and thrombus formation in mice lacking the Ca2+-dependent tyrosine kinase Pyk2

Abstract: Key Points• The tyrosine kinase Pyk2 regulates a p38MAPK-cPLA2 pathway required for thrombin-induced thromboxane A2 production and platelet aggregation.• Pyk2 deletion in mice confers protection against pulmonary thromboembolism and arterial thrombosis.In the present study, we used a knockout murine model to analyze the contribution of the Ca 2؉ -dependent focal adhesion kinase Pyk2 in platelet activation and thrombus formation in vivo. We found that Pyk2-knockout mice had a tail bleeding time that was slightl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 49 publications
3
55
1
Order By: Relevance
“…There are ample published examples in which deletion of a signaling cascade protein causes only modest defects in platelet activation in ex vivo assays, yet the protein contributes significantly to in vivo hemostasis and thrombosis. 56,[76][77][78][79] In a recent example, STXBP5 deletion yielded modest defects on dense granule release but was absolutely required for hemostasis in the tail transection model and for thrombosis in the FeCl 3 -induced carotid injury model. 80 Therefore, it is possible that the sensitivity of the ex vivo assays we employed are insufficient to fully delineate the effects of deleting the autophagy machinery.…”
Section: Autophagy In Hemostasis and Thrombosis 1229mentioning
confidence: 99%
“…There are ample published examples in which deletion of a signaling cascade protein causes only modest defects in platelet activation in ex vivo assays, yet the protein contributes significantly to in vivo hemostasis and thrombosis. 56,[76][77][78][79] In a recent example, STXBP5 deletion yielded modest defects on dense granule release but was absolutely required for hemostasis in the tail transection model and for thrombosis in the FeCl 3 -induced carotid injury model. 80 Therefore, it is possible that the sensitivity of the ex vivo assays we employed are insufficient to fully delineate the effects of deleting the autophagy machinery.…”
Section: Autophagy In Hemostasis and Thrombosis 1229mentioning
confidence: 99%
“…In addition, we found that Pyk2 inhibition had no effect on ADP-induced platelet aggregation in aspirin-treated platelets, which is consistent with a previous study (41) showing that there was no difference in ADP-induced platelet aggregation from WT or TxA 2 receptor null mice. Recent study (42) has characterized the platelets from Pyk2 knock-out mice and no significant differences are observed between WT and Pyk2 knock-out mice. In addition, arachidonic acid induces normal platelet aggregation in Pyk2-deficient platelets, and Pyk2 is linked to cPLA2 activation (42).…”
Section: Discussionmentioning
confidence: 99%
“…Recent study (42) has characterized the platelets from Pyk2 knock-out mice and no significant differences are observed between WT and Pyk2 knock-out mice. In addition, arachidonic acid induces normal platelet aggregation in Pyk2-deficient platelets, and Pyk2 is linked to cPLA2 activation (42). In the experimental model adopted from a previous study (21) to confirm the role of Pyk2 downstream of G 12/13 pathways in TxA 2 generation, we found that G 12/13 pathways failed to substitute for integrin-mediated signaling for TxA 2 generation in the presence of the Pyk2 inhibitor confirming the contribution of Pyk2 downstream of G 12/13 pathways.…”
Section: Discussionmentioning
confidence: 99%
“…11 Among them, Rap1b and the Ser/Thr kinase Akt have been implicated in a IIb b 3 inside-out and/or outside-in signaling in a PI3Kb-dependent manner. 6,19,[31][32][33][34][35][36][37] Using PDK1-deficient mice, it was proposed that the PDK1/Akt axis modulates platelet aggregation and clot retraction. 38 Although the b3 integrin can be phosphorylated on Thr 753 by PDK1 and Akt in vitro 39 , the exact regulatory mechanism involving these kinases remains to be established.…”
Section: Discussionmentioning
confidence: 99%